Farroupilha/RS e a educação (1934-1948): um município pedagógico - Belusso, Gisele (My University, 2021)
The aim of the study is to understand the municipal actions in favor of Education in the municipality of Farroupilha/RS. The time span initiates in 1934 - year of emancipation of Farroupilha -, as it is understood that, from that date on, conditions to constitute local actions in favor of Education emerge, and they go on until 1948, when the municipality received from the Department of Municipal Administrations a new Project of regulation for municipal primary teaching, reorganizing it in different categories: basic primary education and supplementary education, due to Organic Law of Primary Education (1946). This law presents emergency conditions after the end of Estado Novo and the reopening of the Chamber of Councilors. The theoretical-methodological assumptions of Cultural History and of History of Education guided the analysis, mainly by constructions of Burke (1992), Le Goff (1996), Candau (2016), Hall (2000), Chartier (2002) and Certeau (2014). Regarding the support of understanding the pedagogic municipality, Magalhães (2006b, 2014a), Adão y Magalhães (2013; 2014) and Gonçalves Neto, and Carvalho (2015) contribute. Some of the documents that were used to compose the empiric corpus are mailing, petitions, newspapers, interviews, laws, norms, acts, decreets, photographs and plights. From theoretical-methodological assumptions and from the empirical corpus used, I listed analytic categories, having as guiding principle the municipal actions in favor of Education, which were a) transition from school net, b) municipal majors? actions, and c) public investment in Education. From the analysis, some unfolds arose that resulted in the narrative that presents the reconfiguration of the colonies in municipalities, between the end of the 19th century and the beginning of the 20th century, among them, Farroupilha. Due to political emancipation, the municipal administration was organized with new spaces to shelter public bodies, such as the Municipal Mayor's Office and the Police Station, in the central area of the municipality, where the urban space that was gradually rationalized and standardized in local scope was constituted. In the 1930s and 1940s, Farroupilha had options for transportation, communication, electricity, spaces for sociability, and health care. In addition, it was expressive in the export of agricultural products, it had established industries and businesses. The population could be briefly characterized, mostly, by Brazilians who could read and lived in rural areas. Thus, it received a municipal school network previously constituted by other municipalities, and it was up to the public administration to carry out a transition process, taking responsibility, among other actions, for the selection, remuneration, training and supervision of teachers. The municipal school network was made up of isolated classrooms, predominantly in rural areas, which generally functioned in buildings built or donated by the communities. In this process, the analysis of the mayors' actions became significant to understand how they carried out municipal actions in favor of Education. In eight administrative mandates, there were alternations in positions and length of stay, but all subjects cite Education as important and mobilize in innumerable ways to maintain and expand schools and levels of education, articulating with public agents, groups and institutions. The municipality kept most of the students enrolled in municipal primary education and supported the opening and operation of state and confessional schools. Therefore, public investments in Education went beyond what was foreseen in the annual budget laws. So, the thesis is that the municipality of Farroupilha took on an educational project, which was unfolded in effective actions, in coordination with the state and federal government agencies, with local groups, and the Catholic Church, to ensure the supply of schooling and expand the levels of education. These actions were guaranteed by the leadership of the municipality, especially the mayors who made Education a priority, who knew how to make use of the autonomy space and applied the investment of the necessary public resources in school materials, furniture, teaching materials, awards, payment of rents, completion of final exams, civic commemorations, contributions of various orders, acquisition of land, subsidies for professional education, agreements for the offer of secondary education (ginasial), scholarships, school uniforms, public library and payment to teachers (effective, substitutes, assistants), in addition to other professionals, such as the teaching counselor and the director of Public Instruction. Thus, given the evidence presented, Farroupilha is understood, between the years of 1934 and 1948, as a pedagogical municipality [resumo fornecido pelo autor].
O objetivo do estudo é compreender as ações municipais em prol da Educação no município de Farroupilha/RS. O recorte temporal inicia em 1934 - ano da emancipação de Farroupilha -, por compreender que, a partir de então, surgem condições para a constituição de ações locais em prol da Educação, e estende-se até 1948, ano que o município recebeu do Departamento das Prefeituras Municipais um novo projeto de regulamento para o ensino primário municipal, reorganizando-o em distintas categorias: ensino primário fundamental e ensino supletivo, decorrências da Lei Orgânica do Ensino Primário (1946). Tal regulamento tem condições de emergência após o final do Estado Novo e a reabertura da Câmara de Vereadores. Os pressupostos teórico-metodológicos da História Cultural e na História da Educação orientaram a análise, sobretudo com as contribuições de Burke (1992), Le Goff (1996), Candau (2016), Hall (2000), Chartier (2002) e Certeau (2014). Já para ancorar a compreensão do município pedagógico, contribui Magalhães (2006b, 2014a), Adão e Magalhães (2013; 2014) e Gonçalves Neto e Carvalho (2015). Alguns dos documentos mobilizados para compor o corpus empírico são correspondências, abaixo-assinados, jornais, entrevistas, leis, portarias, atos, decretos, fotografias e empenhos. A partir dos pressupostos teórico-metodológicos e do corpus empírico mobilizado, elenquei categorias analíticas, tendo como fio condutor as ações municipais em prol da Educação, as quais foram a) transição da rede escolar, b) ações dos prefeitos municipais e c) investimento público em Educação. A partir da análise, emergiram desdobramentos que resultaram na narrativa que apresenta a reconfiguração das colônias em municípios, entre o final do século XIX e início do século XX, dentre eles Farroupilha. Devido à emancipação política, a administração municipal foi organizada, com novos espaços para abrigar os órgãos públicos, tais como a Prefeitura Municipal e a Delegacia de Polícia, na área central do município, onde constituiu-se o espaço urbano que foi paulatinamente racionalizado e normatizado em âmbito local. Farroupilha contava, nas décadas de 1930 e 1940, com opções de transporte, comunicação, energia elétrica, espaços de sociabilidade e atendimento em saúde. Além disso, era expressiva na exportação de produtos agrícolas, possuía indústrias e comércios estabelecidos. A população pôde ser brevemente caracterizada, em sua maioria, por brasileiros que sabiam ler e residiam em áreas rurais. Assim, Farroupilha recebeu uma rede escolar municipal previamente constituída por outros municípios, e coube a administração pública a realização de um processo de transição, passando a responsabilizar-se, entre outras ações, pela seleção, remuneração, formação e fiscalização dos professores. A rede escolar municipal era composta por aulas isoladas, predominantemente em áreas rurais, que funcionavam, geralmente, em prédios construídos ou cedidos pelas comunidades. Nesse processo, a análise da atuação dos prefeitos tornou-se significativa para compreender como eles efetivaram as ações municipais em prol da Educação. Em oito mandatos administrativos, houve alternâncias nas posturas e tempos de permanência, mas todos os sujeitos elencam a Educação como importante e se mobilizam de inúmeras formas para manter e ampliar escolas e níveis de ensino, articulando-se a agentes públicos, grupos e instituições. A municipalidade manteve a maioria dos alunos matriculados no ensino primário municipal e apoiou a abertura e funcionamento de escolas estaduais e confessionais. Para tanto, os investimentos públicos em Educação foram além do previsto nas leis de orçamento anuais. Assim, a tese é de que o município de Farroupilha assumiu um projeto educativo, que se desdobrou em ações efetivas, em articulação com as instâncias de governo estadual e federal, com os grupos locais e a Igreja Católica, para assegurar a oferta de escolarização e ampliar os níveis de ensino. Essas ações foram garantidas pelo protagonismo do município, em especial, dos prefeitos que elencaram a Educação como prioridade, que souberam fazer uso do espaço de autonomia e despenderam o investimento dos recursos públicos necessários. em materiais escolares, móveis, materiais didáticos, prêmios, pagamento de aluguéis, realização dos exames finais, comemorações cívicas, contribuições de várias ordens, aquisição de terrenos, subvenções ao ensino confessional, convênios para oferta do ensino ginasial, bolsas de estudo, uniformes escolares, biblioteca pública e pagamento dos professores (efetivos, substitutos, auxiliares), além de outros profissionais, como a orientadora de ensino e o diretor da Instrução Pública. Assim, diante das evidências apresentadas, compreende-se Farroupilha, entre os anos de 1934 e 1948, como um município pedagógico [resumo fornecido pelo autor].
Keywords: Educação - História - Farroupilha (RS); Education - History - Farroupilha (RS)